Fibrillin-1 (FBN-1) a new marker of germ cell neoplasia in situ. Issue 1 (December 2016) - Cierna, Z.; Mego, M.; Jurisica, I.; Machalekova, K.; Chovanec, M.; Miskovska, V.; Svetlovska, D.; Kalavska, K.; Rejlekova, K.; Kajo, K.; Mardiak, J.; Babal, P.
Abstract Background Germ cell neoplasia in situ (GCNIS), is preinvasive stage of testicular germ cell tumours (TGCTs). Fibrillins, which are integral components of microfibrils are suggested to be involved in cancer pathogenesis and maintenance of embryonic stem cells pluripotency. The aim of this study was to examine fibrillin-1 (FBN-1) expression in TGCTs patients. Methods Surgical specimens from 203 patients with TGCTs were included into the translational study. FBN-1 expression was evaluated in the tumour tissue, in GCNIS and in adjacent non-neoplastic testicular tissue in all available cases. Tissue samples were processed by the tissue microarray method. FBN-1 was detected by immunohistochemistry using goat polyclonal antibody and the expression was evaluated by the multiplicative quickscore (QS). Results The highest FBN-1 positivity was detected in GCNIS (mean QS = 11.30), with overexpression of FBN-1 (QS >9) in the majority (77.1 %) of cases. Expression of FBN-1 in all subtypes of TGCTs was significantly lower in comparison to expression in GCNIS (allp <0.001). Seminoma had significantly higher expression compared to EC, ChC and TER (allp <0.05), but not to YST (p = 0.84). In non-neoplastic testicular tissue the FBN-1 positivity was very low (mean QS = 0.02). Sensitivity, specificity, positive and negative predictive value of FBN-1 expression for diagnosis of GCNIS were 97.1, 98.8, 98.6 and 97.7 %. Conclusions FBN-1 is overexpressed in TGCTs and especially in GCNIS when compared to non-neoplastic testicular tissue in patients with germ cell tumors and could be involved in germ cell neoplasia in situ development.